Meningkatkan kemampuan pemecahan masalah matematis mahasiswa melalui model project-based learning - Ade Evi Fatimah; Fitry Wahyuni; Fitriani Fitriani (Mahesa Research Center, 2022)
This type of research is known as classroom action research (CAR), and it employs both descriptive and qualitative methods. The purpose of this study was to describe how to improve the mathematical problem-solving abilities of PTI 3E class students at STKIP Al Maksum, with a total of 30 students. This research was carried out in the odd semester of the 2022–2023 academic year. The object of this research is to improve students' mathematical problem-solving skills through the project-based learning (PjBL) model on graph material for discrete mathematics courses. The research instruments used were a test of mathematical problem-solving abilities and observation sheets. The results showed that there was an increase in the number of students who achieved completion in solving mathematical problems in cycle I by 20% and in cycle II by 26.7%. The increase in problem-solving ability has reached the target or process indicator, namely 85% of students who obtain a minimum problem-solving ability percentage of 60% of students who take tests in the learning process.